IgSF9b regulates anxiety behaviors through effects on centromedial amygdala inhibitory synapses. Issue 1 (December 2018) - Babaev, Olga; Cruces-Solis, Hugo; Piletti Chatain, Carolina; Hammer, Matthieu; Wenger, Sally; Ali, Heba; Karalis, Nikolaos; de Hoz, Livia; Schlüter, Oliver; Yanagawa, Yuchio; Ehrenreich, Hannelore; Taschenberger, Holger; et al.
Abstract Abnormalities in synaptic inhibition play a critical role in psychiatric disorders, and accordingly, it is essential to understand the molecular mechanisms linking components of the inhibitory postsynapse to psychiatrically relevant neural circuits and behaviors. Here we study the role of IgSF9b, an adhesion protein that has been associated with affective disorders, in the amygdala anxiety circuitry. We show that deletion of IgSF9b normalizes anxiety-related behaviors and neural processing in mice lacking the synapse organizer Neuroligin-2 (Nlgn2), which was proposed to complex with IgSF9b. This normalization occurs through differential effects of Nlgn2 and IgSF9b at inhibitory synapses in the basal and centromedial amygdala (CeM), respectively. Moreover, deletion of IgSF9b in the CeM of adult Nlgn2 knockout mice has a prominent anxiolytic effect. Our data place IgSF9b as a key regulator of inhibition in the amygdala and indicate that IgSF9b-expressing synapses in the CeM may represent a target for anxiolytic therapies. IgSF9b is a synaptic adhesion protein that has been linked to psychiatric disorders. Here the authors show that deletion of IgSF9b regulates anxiety-like behaviour in mice by increasing inhibitory synaptic transmission in the centromedial amygdala.